A comparative study of extradition practise between Malaysia and United Kingdom / Afif Ahmayuddin, Darren N. Punai and Nur Afiah Ahmad Radzi - Ahmayuddin, Afif; N. Punai, Darren; Ahmad Radzi, Nur Afiah (2010)
This legal research is conducted with an aim to compare and analyse the extradition practise in Malaysia and United Kingdom. Even though most countries especially Malaysia, follow the system of United Kingdom, it lacks certain safeguard that an extradite requires. Thus, this research will focus on the protection of the Human Right in accordance with the case of extradition. The scope of this legal research is on the legislation of extradition and its relation to the protection of human rights. A comparative analysis study has been conducted to examine the distinction between Malaysia and United Kingdom. This legal research will be based on the secondary sources from the Law Library of Universiti Teknologi MARA (UiTM). We have utilized legislation, newspaper articles, online articles, books, cases, and other appropriate sources that relate to the extradition process in Malaysia as well as United Kingdom to analyse the provisions and practices of the laws of both states. It is hoped that this legal research will provide a comprehensive discussion on the fundamental rights of an individual in regards to extradition process in Malaysia and proposed amendments or suggestion to the current law to give better protection to all parties involved in an extradition case.